ANALYSIS OF THE IMMUNIZATION PROGRAM IN TRENGGALEK DISTRICT, EAST JAVA PROVINCE IN 2019 - 2021 - Sagita, Insharie Arie; Hidajah, Atik Choirul; Ratgono, Antonius (HEARTY, 2024)
The immunization program is aimed to reach herd immunity, is requires high immunization coverage. The coverage of Universal Child Immunization (UCI) at the Village level in Trenggalek District for the period 2019–2021 still had not reached the target (100%), 91.08% in 2019, 92.36% in 2020, and 89.17% in 2021. This study aimed to identify the causes of the problem and suggest alternative solutions. This observational descriptive study was conducted at the Trenggalek District Health Office in January 2023. Informants were 17 people (4 officers of the health office who were responsible for the immunization program and 13 immunization coordinators from the Public Health Center/PHC which in 2019–2021 had not reached the UCI coverage at Village level). Identification of root causes was using a fishbone diagram and determining the priority of root causes to be intervened with using the Capability, Accessibility, Readiness, and Leverage (CARL) method which was done through brainstorming with all respondents. There were identified 11 root causes of not achieving the UCI coverage at the Village level. The dominant factor affecting the root problem was the officers (81.81%). The root problem that received the highest score with the CARL method was the immunization officers did not give communication, information, and education to parents optimally. This happened because the officers only focused on the number of targets to reach. In each PHC, there needs to be a team that gives communication, information, and education to assist immunization officers in providing education and information about immunization. The Immunization Officer in the District Health Office needs to monitor and evaluate the immunization services and give feedback to the PHC periodically.